A spatial analysis of inter-regional patient mobility in Italy - Emanuela Marrocu; Silvia Balia; Rinaldo Brau (European Regional Science Association (ERSA), 2016)
Free patient mobility among autonomous providers has been often considered an effective stimulus for enhancing healthcare. However, some jurisdictions may underperform due to the existence of economies of scale and spatial spillovers. Where regions assume the costs of providing care to residents, this could challenge the sustainability of regional budgets in a decentralised National Health Service (NHS) and put at risk universalism and equity of health care. We use a ten years (2001-2010) panel of Italian data on hospital discharges to assess the determinants of inter-regional mobility and to distinguish between factors related with policies pursued by the regional health authorities from extra-regional (neighbouring regions or national-level) factors. Data on hospital discharges are merged with a set of variables on salient features of hospital care services in each Regional Health System (RHS) and with information on demographic and economic characteristics of Italian regions. We analyse bilateral Origin-to-Destination (OD) flows between any two regions by means of a gravity regression model that includes a rich set of push and pull factors. Compared to previous studies, mainly performed on cross-section samples, the longitudinal dimension of the data enables us to estimate a nonlinear conditionally correlated random effects dynamic model that accounts for region-pair-specific unobservable heterogeneity. Moreover, we address the issue of cross-regional dependence arising from the existence of regional spillovers by applying recent advances in spatial econometrics (Elhorst, 2014; Vega and Elhorst, 2015). The model is estimated for total inter-regional patient flows and for specific types of hospital admission, namely surgery, medicine and cancers. Finally, the estimation results are used to analyse specific what-if scenarios relevant to the health authorities for the national and sub-national management of services. Our main results suggest that, beside regional population and income, local supply factors such as hospital capacity and technology endowment, clinical specialization and performance indicators are important drivers of patient mobility. Moreover, geography matters and spatial proximity plays a relevant role in reinforcing inter-regional mobility patterns. Our econometric analysis has also detected a mildly explosive dynamics in inter-regional patient mobility over time. This result, coupled with the significant role played by factors not directly controlled by regional policy-makers and RHS managers (e.g. population, GDP per capita and spatial spillovers), might induce a polarisation between the group of the richest, most populated and best performing regions, which are increasingly capable of attracting more patients, and the group of the weakest regions, with growing patient outflows and severe financial and organizational problems. These considerations call for a thorough assessment of the long-run sustainability of the current decentralised NHS. RHS budget autonomy could not be entirely consistent with free patient choice. This opens a more general discussion on whether and to what extent the health financing system would require the introduction of appropriate equalising compensation schemes aimed at neutralising the financial consequences of mobility and, eventually, at guaranteeing universalism and equity in healthcare.
Keywords: C23; I18; H75; R23; R50; 330; regional health systems; hospital admissions; gravity model; nonlinear gravity panel model; spatial spillovers